Molecular cytogenetic and genetic aspects of globozoospermia: a review. (10th May 2012) - Perrin, A.; Coat, C.; Nguyen, M. H.; Talagas, M.; Morel, F.; Amice, J.; De, M.
Summary Infertility is estimated to affect up to 15% of couples of reproductive age. Among the male factors, globozoospermia (also called round‐headed sperm syndrome) is a rare type of teratozoospermia accounting for <0.1% of male infertility. Lack of acrosome, whose production is a postmeiotic event in spermatogenesis, and round sperm head are its main characteristics. The acrosomeless spermatozoon is unable to go through the zona pellucida and fuse with the oolemma of the oocyte, and fertilisation failures have been attributed to a deficiency in oocyte activation capacity, even when intracytoplasmic sperm injection (ICSI) is attempted. The pathogenesis of this anomaly is still unclear but genetic factors are likely to be involved. DNA fragmentation rate has been reported for 16 globozoospermic males, usually using the terminal uridine nick‐end labelling (TUNEL) assay. Most of the patients had a DNA fragmentation index (DFI) higher than that in fertile men. The rate of aneuploidy for some specific chromosomes was increased in 12 among the 26 globozoospermic males reported in the literature. The same results (high DFI and aneuploidy rates) were observed in infertile males compared to fertile men, notably in those with oligoasthenozoospermia or teratozoospermia, independently of the origins. Mutations or deletions in three genes, SPATA16, PICK1 and DPY19L2, have been shown to be responsible for globozoospermia. Proteins coded by the first two genes localise to the Golgi apparatus and the proacrosomal granules that are transported in the acrosome. It is likely that other proteins involved in the acrosome formation remain to be identified.